Optical properties of titanium oxynitride thin films and application in selective solar absorber - Zhang, Jun (2018)
The selective solar absorber (SSA) is one of the key units in the concentrated solar power (CSP) system, which is promising for generating renewable and clean energy with solar energy. The titanium oxynitride (TiNxOy) thin film based SSA has drawn a lot of attention due to many advantages, such as environmental friendliness, low cost, and excellent optical property. In this thesis, the optical properties of TiNxOy thin films have been investigated and the SSA based on TiNxOy thin film has been designed and modeled. The TiNxOy thin films were fabricated by radio frequency (RF) magnetron sputtering system and have been characterized systematically with various techniques: X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), atomic force microscope (AFM), transmission electron microscope (TEM), spectroscopic ellipsometry (SE), Hall effect measurement, spectrophotometer, etc. The localized surface plasmon resonance (LSPR) effect of the TiN nanoparticles, which were confirmed by high resolution TEM image, plays an important role in the optical properties of the TiNxOy thin films. Considering LSPR effect, free electron absorption and interband transitions, the dielectric function of the TiNxOy thin films was characterized by SE. It is found that the dielectric function of the TiNxOy layer is significantly affected by the N2 flow rate during the sputtering deposition process as a result of the tuning of N/O ratio. A single TiNxOy thin film based SSA with the structure of SiO2-TiO2-TiNxOy-Cu has been designed. SiO2 and TiO2 thin films form a double-layer anti-reflection coating (ARC). A TiNxOy thin film serves as an absorbing layer. The optical properties of TiNxOy thin films can be easily adjusted by the N2 flow rate, which is an effective way to optimize the performance of SSA. Due to the large free electron concentration, a Cu substrate is used as an infrared reflector. The SSA based on the TiNxOy layer deposited with a N2 flow rate of 2 sccm achieves a total solar absorptance of 94.44% and a total thermal emittance of 6.15% at the temperature of 400 ℃. A double TiNxOy thin films based SSA is also proposed in the thesis. In the SSA, a TiNxOy thin film with a low N/O ratio (TiNO_L) and a TiNxOy thin film with a high N/O ratio (TiNO_H) are utilized. At the same time, three absorption mechanisms in the TiNxOy thin films have been modeled: LSPR, free electron absorption and interband transitions. Because TiNO_H has a higher free electron concentration than that of TiNO_L, the absorption due to both the LSPR and free electron absorption in TiNO_H is found larger than that in TiNO_L. The absorption caused by the interband transitions in the TiNO_L and TiNO_H is close to each other. By using TiNO_L and TiNO_H, a double TiNxOy layer based SSA with the structure of SiO2-TiO2-TiNO_L-TiNO_H-Cu has been fabricated. It is found that the double TiNxOy layer based SSA has a wider low reflectance range than that of single TiNxOy layer based SSA. A low cost and high thermal stable SSA with the structure of SiO2-TiNxOy-W-Cu has been fabricated on glass substrate. In the SSA, to improve the thermal stability, W-Cu thin film structure is used to serve as an infrared reflector. Without W thin film, the reflectance in both visible and infrared ranges of the SSA increases due to the crystallization of the Cu layer at elevated temperatures. With a 15 nm W thin film, the increase of the reflectance in the visible range can be suppressed to maintain a high solar absorptance, while a high infrared reflectance can be maintained to achieve a low thermal emittance.